Project-Based Learning in Science Learning: A Literature Review - Thufail Mujaddid Al-Qoyyim; Wardi Kurniawan (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2025)
Project-Based Learning (PjBL) is increasingly recognized as a transformative pedagogical model that addresses the evolving demands of 21st-century science education. This article presents a comprehensive literature-based analysis of the definition, instructional framework, practical implementation, advantages, and challenges of PjBL, particularly in the context of science learning. PjBL emphasizes student-centered, inquiry-driven learning experiences that are grounded in real-world problems, promoting not only academic achievement but also the development of higher-order thinking skills, collaboration, creativity, and scientific literacy. Through a structured instructional syntax involving driving questions, project planning, collaborative execution, presentation, and reflection, PjBL fosters meaningful engagement and active participation among learners. Case studies across educational levels demonstrate its adaptability and effectiveness in enhancing students' scientific reasoning and real-life application. Despite notable challenges such as resource limitations, time constraints, and the need for teacher preparedness, the benefits of PjBL in fostering deep, interdisciplinary learning and student agency are significant. The article concludes by emphasizing the importance of strategic planning, ongoing teacher training, and institutional support to ensure the successful integration of PjBL into science curricula. Overall, PjBL offers a promising pathway for cultivating innovative, reflective, and socially responsible learners capable of addressing complex global challenges.